Oenanthe javanica Ethanolic Extract Alleviates Inflammation and Modifies Gut Microbiota in Mice with DSS-Induced Colitis - Ui-Jin Bae; Ha-Na Jang; Sung-Hyen Lee; Ji-Young Kim; Gi-Chang Kim (MDPI AG, 2022)
Oenanthe javanica, commonly known as water dropwort, has long been used to treat acute and chronic hepatitis, abdominal pain, alcohol hangovers, and inflammation in various traditional medicine systems in Asia. However, whether O. javanica has beneficial effects on colitis-induced intestinal damage remains elusive. This study tested the hypothesis that O. javanica has anti-inflammatory and antioxidant activities in mice with dextran sulfate sodium (DSS)-induced colitis. First, treatment of O. javanica ethanol extract (OJE) inhibited the production of inflammatory cytokines in lipopolysaccharide-affected macrophages. Second, in mice with DSS-induced colitis, OJE administration reduced pathological damage to the colon while alleviating weight gain and decreasing colon length, including inflammation and mucosal necrosis. In addition, OJE significantly (p < 0.01) restricted the activation of nuclear factor-κB (NF-κB) and the secretion of pro-inflammatory mediators and increased the expression of Nrf2-phase 2 antioxidant enzymes. The results of 16S rRNA gene sequencing workflows for taxonomic assignment analysis confirmed that the diversity (richness and evenness) of fecal microbiota was markedly elevated in the OJE group. OJE administration reduced the abundance of Proteobacteria including Escherichia and increased the abundance of the genus Muribaculum. These results suggested that OJE exerts beneficial effects on inflammation and gut microbial composition in a mouse model of colitis.